A comparison of blood toxicology in fatalities involving alcohol and other drugs in patients with an opioid use disorder treated with methadone, buprenorphine, and implant naltrexone. (3rd March 2020) - Kelty, Erin; Hulse, Gary; Joyce, David
ABSTRACT: Background : Methadone, buprenorphine, and implant naltrexone have comparable efficacy in preventing death from drug intoxication during treatment, but there may be differences between treatments in the specific drugs contributing to death and in the risk of death during different phases of treatment. Objective : The objective of this study was to compare concentrations of individual drugs in decedents for evidence that the three medications use to treat opioid use disorders differed in the protection they offered against fatal overdose. Methods : Fatalities with a primary or co-diagnosis of alcohol or other drug poisoning in patients treated with methadone (n = 66, 74.2% male), buprenorphine (n = 54, 74.1% male), or naltrexone (n = 28, 85.7% male) were identified by combining treatment (Monitoring of Drugs of Dependence System and clinical records) and mortality records (Western Australian Death Registry). Quantitative postmortem blood drug analysis data were obtained for drug-related deaths. The presence/absence of drugs were compared between the three medication groups and between phases of treatment (on-treatment/off-treatment). Results : Opioids (89.8%) and benzodiazepines (76.2%) were most commonly identified in postmortem blood. The three medication groups did not differ materially in the drugs present postmortem, except that alcohol was less prevalent in naltrexone-treated cases. Morphine or heroin intoxication was implicated in more patients dying off-treatment than on-treatment but levels of morphine and other drugs were comparable across the two phases. Conclusion : Comparisons of postmortem concentrations of specific drugs indicated that patients treated with methadone, buprenorphine, and implant naltrexone had comparable susceptibilities to lethal co-intoxication and that similar drug mixtures contributed to death.